Improving survey questions design and evaluation - Fowler, Floyd J., Jr (Applied social research methods series, 1995)
Covers how to write good questions aimed at collecting information about objective facts and events, some alternative methods for attacking common measurement problems, how to evaluate the extent to which questions are consistently understood and administered, and how to evaluate the data resulting from a set of questions.